AI-Era Digital Literacy: Cultivating Honesty in Islamic Education - Mohammad Mustari; Sri Nurhayati; Syarifuddin Syarifuddin (UIN Sunan Gunung Djati Bandung, 2026)
This qualitative case study at SMP Prima Cendikia Islami (PCI), Bandung, examines integrating AI-driven digital literacy with honesty education in a faith-based junior high school. Using purposive sampling of leaders, teachers, students, and parents, data from interviews, focus groups, document analysis, and observations underwent thematic analysis with triangulation for rigor. Findings show AI platforms (e.g., TAKJUP, LMS, Parent Information System) embed moral reasoning via formative monitoring, sustaining top national character rankings. High teacher training and student-led clinics promote ethical accountability, proving pedagogical design determines AI's moral impact. Faith-based schools can thus harmonize tech innovation with values education, offering a scalable model. Future research should explore longitudinal moral outcomes and validated honesty measures.